Haplotype phasing of a bipolar disorder pedigree revealed rare multiple mutations of SPOCD1 gene in the 1p36–35 susceptibility locus - Takamatsu, Gakuya; Yanagi, Kumiko; Koganebuchi, Kae; Yoshida, Fuyuko; Lee, Jun-Seok; Toyama, Kanako; Hattori, Kotaro; Katagiri, Chiaki; Kondo, Tsuyoshi; Kunugi, Hiroshi; Kimura, Ryosuke; Kaname, Tadashi; et al. (Journal of affective disorders, 2022)
The etiology of bipolar disorder (BD) is poorly understood. Considering the complexity of BD, pedigree-based sequencing studies focusing on haplotypes at specific loci may be practical to discover high-impact risk variants. This study comprehensively examined the haplotype sequence at 1p36–35 BD and recurrent depressive disorder (RDD) susceptibility loci. We surveyed BD families in Okinawa, Japan. We performed linkage analysis and determined the phased sequence of the affected haplotype using whole genome sequencing. We filtered rare missense variants on the haplotype. For validation, we conducted a case-control genetic association study on approximately 3000 Japanese subjects. We identified a three-generation multiplex pedigree with BD and RDD. Strikingly, we identified a significant linkage with mood disorders (logarithm of odds [LOD] = 3.61) at 1p36–35, supported in other ancestry studies. Finally, we determined the entire sequence of the 6.4-Mb haplotype shared by all affected subjects. Moreover, we found a rare triplet of missense variants in the SPOCD1 gene on the haplotype. Notably, despite the rare frequency, one heterozygote with multiple SPOCD1 variants was identified in an independent set of 88 BD type I genotyping samples. The 1p36–35 sequence was obtained from only a single pedigree. The replicate sample was small. Short-read sequencing might miss structural variants. A polygenic risk score was not analyzed. The 1p36–35 haplotype sequence may be valuable for future BD variant studies. In particular, SPOCD1 is a promising candidate gene and should be validated. •We found a multiplex pedigree with bipolar disorder (BD) and depression.•We detected significant linkage at 1p36–35, a potential risk locus for BD.•We determined the entire phased sequence of the 1p36–35 affected haplotype.•We found rare missense variants in SPOCD1 candidate gene on this haplotype.•The multiple SPOCD1 variants were found in a replicate set of BD.